For a geography of existences: interview with professor and geographer Catia Antonia da Silva - Dorival Bonfá Neto; Júlio César Suzuki (Geografares, 2025)
Catia Antonia da Silva is a native of Rio de Janeiro, an educator, researcher, and full professor in the Department of Geography at the State University of Rio de Janeiro (UERJ). She graduated in Geography from the Federal University of Rio de Janeiro (UFRJ) in 1987, holds a master’s degree in Urban and Regional Planning from UFRJ (1994), and earned her PhD in Geography from the same university in 2002. Her work stands out in topics such as socio-environmental conflicts, traditional peoples and communities in urban contexts, artisanal fishing, and teaching and research methodology. Based on her studies, she developed the category of Geography of Existences to reflect on the invisibilized, those with “mutilated citizenships.” She is the leader of the Research and Extension Group “Urban, Territory, and Contemporary Changes” and the founder and coordinator of the Socio-Environmental Observatory of Sepetiba Bay. She served as director of the Extension Department at UERJ (2016–2019) and vice-rector of Policies and Student Assistance at UERJ (2020–2023). The interview with Catia was conducted virtually on March 26, 2024, at 3 p.m. (Brasilia time).